1997
DOI: 10.1002/(sici)1096-9861(19971020)387:2<167::aid-cne1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in synaptogenesis in human cerebral cortex

Abstract: The formation of synaptic contacts in human cerebral cortex was compared in two cortical regions: auditory cortex (Heschl's gyrus) and prefrontal cortex (middle frontal gyrus). Synapse formation in both cortical regions begins in the fetus, before conceptual age 27 weeks. Synaptic density increases more rapidly in auditory cortex, where the maximum is reached near postnatal age 3 months. Maximum synaptic density in middle frontal gyrus is not reached until after age 15 months. Synaptogenesis occurs concurrentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

142
1,870
11
35

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,679 publications
(2,097 citation statements)
references
References 32 publications
142
1,870
11
35
Order By: Relevance
“…In turn, this might lead to activation of a large number of less specific axons, rather than a few specialized neurons (Innocenti and Price 2005). Since synaptic pruning is thought to be completed by around 12 years of age in the auditory cortex (Huttenlocher and Dabholkar 1997), these aberrant cortical connections might last and be stabilized due to the long-term auditory deprivation in our prelingually deaf group (Innocenti and Price 2005;Uhlhaas and Singer 2011). Kral et al (2006) demonstrated that the naïve auditory cortex of congenitally deaf cats has a reduced sensitivity to auditory input, leading to a smeared representation of auditory stimuli with a deficient representation of auditory features including loss of tonotopy (Kral et al 2006).…”
Section: Caep Differences Between Postlingually and Prelingually Deafmentioning
confidence: 97%
See 1 more Smart Citation
“…In turn, this might lead to activation of a large number of less specific axons, rather than a few specialized neurons (Innocenti and Price 2005). Since synaptic pruning is thought to be completed by around 12 years of age in the auditory cortex (Huttenlocher and Dabholkar 1997), these aberrant cortical connections might last and be stabilized due to the long-term auditory deprivation in our prelingually deaf group (Innocenti and Price 2005;Uhlhaas and Singer 2011). Kral et al (2006) demonstrated that the naïve auditory cortex of congenitally deaf cats has a reduced sensitivity to auditory input, leading to a smeared representation of auditory stimuli with a deficient representation of auditory features including loss of tonotopy (Kral et al 2006).…”
Section: Caep Differences Between Postlingually and Prelingually Deafmentioning
confidence: 97%
“…We addressed this cascade of cortical developmental events by recording CAEPs in adult cochlear implant users who became deaf before the age of 2 years and received their implants during adulthood and had therefore much longer durations of auditory deprivation than the late implanted, prelingually deaf children in the abovementioned studies. The long period of auditory deprivation will most likely prevent neural maturation processes, which may normally occur throughout adolescence, such as synaptic pruning (Huttenlocher and Dabholkar 1997), to emerge after cochlear implantation. Extrapolating the results of Gordon et al (2008) a (near-) normal N1 would be possible in these subjects; based on the other studies their CAEPs are expected to lack a significant N1.…”
Section: Introductionmentioning
confidence: 99%
“…Fine-tuning of visual processing may entail the elimination (pruning) of redundant synapses and the facilitation of inter-areal connectivity (Huttenlocher and Dabholkar, 1997;Thatcher, 1992). In this view, neuronal development may progress towards increasingly sparse representations and higher temporal synchronization leading to more efficient stimulus processing.…”
Section: Lifespan Differences In Sensory Coding Mechanismsmentioning
confidence: 99%
“…During this period of increasing marijuana use, continued neuromaturation includes synaptic refinement, myelination, and improved cognitive and functional efficiency (Huttenlocher and Dabholkar, 1997;Giedd et al, 1999;Casey et al, 2000;Paus et al, 2001;Gogtay et al, 2004). The potential long-term consequences of marijuana use on the developing adolescent brain have not been well delineated, but they could have major implications for academic, occupational and social achievement.…”
Section: Introductionmentioning
confidence: 99%